1982
DOI: 10.1152/ajprenal.1982.243.4.f311
|View full text |Cite
|
Sign up to set email alerts
|

Renal carbonic anhydrase

Abstract: Carbonic anhydrase is a zinc metalloenzyme widely distributed throughout the tissues of the body. This enzyme exists in a number of isozymic forms in most mammalian species. Significant advances over the past decade have been made in characterizing the nature of renal carbonic anhydrase. In the kidney, this enzyme is thought to play a pivotal role in urinary acidification and bicarbonate reabsorption. Two distinct isozymes of carbonic anhydrase have now been identified in the mammalian kidney. A soluble cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 0 publications
3
48
0
Order By: Relevance
“…4 present study describes changes in the majority cell type, the principal cell, distinguished by a relatively low fractional resistance (fla), and significant amiloride-and barium-sensitive ion conductances in the apical cell membrane (23). It is the latter cell type that has been identified as the site of mineralocorticoid action in the cortical collecting tubule (9,23,29). We conclude from the present study that a high K intake also modulates Na and K transport in principal cells.…”
Section: Discussionsupporting
confidence: 61%
“…4 present study describes changes in the majority cell type, the principal cell, distinguished by a relatively low fractional resistance (fla), and significant amiloride-and barium-sensitive ion conductances in the apical cell membrane (23). It is the latter cell type that has been identified as the site of mineralocorticoid action in the cortical collecting tubule (9,23,29). We conclude from the present study that a high K intake also modulates Na and K transport in principal cells.…”
Section: Discussionsupporting
confidence: 61%
“…The complex H'ATPase labeling pattern seen in the distal nephron and the initial parts of the collecting duct system reveals heterogeneity of the non-intercalated cells in tubular epithelia that is also reflected by morphological differences (4). Labeling of these segments with antibodies against other antigens such as vitamin D-dependent calcium binding protein (50), Tamm-Horsfall glycoprotein (51), and carbonic anhydrase (38)(39)(40), also demonstrates the heterogeneous nature of these cells. Functional studies on the response of isolated, microdissected distal segments to hormones and various physiological stimuli is probably attributable to the presence of different cell types in the various regions examined (52).…”
Section: Immunocytochemistrymentioning
confidence: 98%
“…Recent morphologic studies focusing on the CCT intercalated cell have suggested a role for C02 in the regulation of CCT HCO absorption. Of the two cell types identifiable by light microscopy, it is the intercalated, or mitochondrial-rich cell, rather than the principal cell that is thought to reabsorb HCO-via active H+ secretion (6,(11)(12)(13)(14)(15)(16)(17). Electron microscopy ofthis cell shows significant increases in the apical cell membrane surface area when experimental animals were subjected to 4 h of respiratory acidosis (16,17).…”
Section: Introductionmentioning
confidence: 99%